Reproducing Celibacy: Nuns' Households in Nineteenth-Century New Mexico Territory. Issue 4 (4th August 2022) - Jacobson, Danae
Abstract: This article explores the material and cultural households that Catholic nuns, the Sisters of Loretto, built in New Mexico Territory in the 1850s through 1870s.   In some ways, these households served a similar function as other White households in the U.S. settler empire. However, given the specific situation in New Mexico Territory—where Nuevomexicanos remained dominant in politics and demographics after U.S. conquest, where Catholicism was widespread, and where the nuns became a majority Spanish-speaking, New Mexican congregation—the Sisters of Loretto ended up playing a complicated and surprising role in both U.S. and Catholic colonialism in New Mexico. Through an examination of the nuns' built environment, rituals, and novitiate, the article explores how this unconventional household reproduced itself, within the context of the U.S. settler empire and Catholic colonialism. Although the Sisters of Loretto's arrival in Santa Fe was predicated on U.S. conquest, the expected narrative of easterners go west to conquer and Americanize is complicated by the concurrent Catholic colonialism, the nuns' gender, as well as the deep history of Catholicism in New Mexico Territory. In the end, New Mexican women, both wealthy and poor, are the protagonists of this story. Given the power of New Mexican women in the community and its decision to conduct ritual life in Spanish, this household worked to constrain the Americanization of New Mexico Territory in the face of U.S. conquest and the anti-New Mexican push of Catholic priests from the U.S. and Europe.